2015
DOI: 10.1159/000382077
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fragmented QRS with Subclinical Left Ventricular Dysfunction in Patients with Obstructive Sleep Apnea

Abstract: Objective: We aimed to investigate whether fragmented QRS (fQRS) is associated with subclinical left ventricular (LV) dysfunction in patients with obstructive sleep apnea (OSA). Subjects and Methods: A total of 141 patients with OSA who had normal LV ejection fraction (LVEF) were included in the study. The fQRS was defined as the presence of an additional R wave, notching of R or S wave or the presence of fragmentation in 2 contiguous electrocardiography (ECG) leads. Subclinical LV dysfunction was defined as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Using this method, deterioration in LV function can be identified before overt heart failure [18]. Several studies have reported that the MPI is not affected by blood pressure, heart rate, valvular regurgitation, ventricular geometry, preload, and afterload in patients who are in a supine position [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, deterioration in LV function can be identified before overt heart failure [18]. Several studies have reported that the MPI is not affected by blood pressure, heart rate, valvular regurgitation, ventricular geometry, preload, and afterload in patients who are in a supine position [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…SA, both the obstructive and central types, is one of the most frequently occurring comorbidities in HF, being present in over 50% of patients, regardless of the type of HF (with reduced or preserved left ventricular ejection fraction) [6-8]. SA proved to be prevalent in our patient population (unselected cases hospitalized with acute HF), being predominantly of the obstructive type.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal impulse conduction creates a milieu for VA through reentry mechanisms and fQRS complexes are a predictor of cardiovascular death in patients with structural heart disease [ 88 , 90 ]. Recent studies found fQRS in patients with OSA (independently of obesity), suggestive of electrical myocardial remodeling [ 87 , 91 , 92 ]. One of the mechanisms thought to be responsible for fQRS is cellular apoptosis and interstitial fibrosis in cardiac structure, which may be secondary to chronic hypoxia, metabolic abnormalities and oxidative stress [ 87 , 91 , 92 ].…”
Section: Ecg Predictors Of Ventricular Arrhythmias In Osa Patientsmentioning
confidence: 99%